1991
DOI: 10.1111/j.1365-2214.1991.tb00676.x
|View full text |Cite
|
Sign up to set email alerts
|

Models of parent partnership and child development centres

Abstract: Four models (and an emergent fifth model) of parent partnership are described and their relevance to UK child development centres is explored. Clinical, management and service development issues are drawn out.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 9 publications
0
33
0
Order By: Relevance
“…Skilled professionals will no longer become concerned solely with their own disciplinary boundaries, but with their capabilities as empathetic human beings and their disciplinary skill base in order to enhance the lives of the families that they support. They will need to use an empowerment approach (Appleton & Minchcom, 1991) that recognises the family as a system, with its own social network and the right to a choice of services and levels of engagement. Negotiation (Dale, 1996) will be a key feature of their practice and, where there are differences between professionals and families, there will be joint decision-making based upon shared perspectives.…”
Section: Towards a Transdisciplinary Approachmentioning
confidence: 99%
“…Skilled professionals will no longer become concerned solely with their own disciplinary boundaries, but with their capabilities as empathetic human beings and their disciplinary skill base in order to enhance the lives of the families that they support. They will need to use an empowerment approach (Appleton & Minchcom, 1991) that recognises the family as a system, with its own social network and the right to a choice of services and levels of engagement. Negotiation (Dale, 1996) will be a key feature of their practice and, where there are differences between professionals and families, there will be joint decision-making based upon shared perspectives.…”
Section: Towards a Transdisciplinary Approachmentioning
confidence: 99%
“…(Parent) 12 Parent control and the professional-patient relationship Professionals' attitudes to services for disabled children are gradually moving from one dominated by the ''expert'' paternalistic professional to an ''empowerment'' model. [14][15][16] Paternalism is an attitude of mind in which the professional feels that they know what is best for the parents and so does not treat them as responsible adults and equal partners. The manner in which professionals communicate with parents can carry hidden messages, leaving the parent feeling they are not competent to take part in decision making and need to leave that to others: 17 ''Billy's hospital consultant doesn't call me Mrs A, but 'mum'.''…”
Section: Disability Stress and Copingmentioning
confidence: 99%
“…However, a careful study of health visitors’ case loads showed no consistent pattern to the delivery of preventative programmes designed to ameliorate the effects of disadvantage 11. In addition, difficulties of parent partnerships with professionals can be a blurring of theory and practice,12 13 degenerating into a quagmire of paternalism,14 tokenism,15 and feminism 16. Consequently, alternative approaches have involved other mothers or non-professionals as advocates 17…”
Section: Discussionmentioning
confidence: 99%